Veins extensions to implement a message based algorithm for Dynamic Traffic Assignment in VANETs simulations - Arellano, Wilmer; Mahgoub, Imad; Ilyas, Mohammad (2014 11th Annual High Capacity Optical Networks and Emerging/Enabling Technologies (Photonics for Energy), 2014)
Vehicular Ad hoc NETworks (VANETs) are a subclass of Mobile Ad hoc NETworks (MANETs) and represent a relatively new and very active field of research. VANETs will enable in the near future applications that will dramatically improve roadway safety and traffic efficiency. There is a need to increase traffic efficiency as the gap between the traveled and the physical lane miles keep increasing. The Dynamic Traffic Assignment problem (DTA) tries to dynamically distribute vehicles efficiently on the road network and in accordance with their origins and destinations. VANET environments will constitute the communication backbone that will enable DTA applications. Simulations play an important role in evaluating approaches to these applications as physical test beds are difficult to implement and cost prohibitive. We present extensions to Vehicles in Network Simulation (Veins), a hybrid simulator that incorporates the widely used Simulation of Urban Mobility (SUMO) and the renowned discrete event simulation environment OMNET++. These extensions allow for easy traffic assignment on Veins under program control by using information from broadcasted messages. We propose and simulate algorithm for DTA in VANETs. To demonstrate traffic improvements we use the algorithm in the presence of accidents.